Building Windows 8.1 Apps from the Ground Up - Garofalo, Emanuele; Liccardi, Antonio; Aponte, Michele (Apress : Imprint: Apress, 2013)
This book is the perfect introduction for anyone wanting to create sophisticated Windows 8 apps for the first time. Assuming only a basic knowledge of HTML and CSS we'll walk you through the development process using C# and VB. The book will familiarize you with the tools you'll need to use in order to make the most of Windows' stunning new features. You'll discover how to take advantage of the built-in functionality to create high quality user experiences.